2017
DOI: 10.1007/s12080-017-0335-2
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime reproductive output: individual stochasticity, variance, and sensitivity analysis

Abstract: Lifetime reproductive output (LRO) determines per-generation growth rates, establishes criteria for population growth or decline, and is an important component of fitness. Empirical measurements of LRO reveal high variance among individuals. This variance may result from genuine heterogeneity in individual properties, or from individual stochasticity, the outcome of probabilistic demographic events during the life cycle. To evaluate the extent of individual stochasticity requires the calculation of the statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
111
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(111 citation statements)
references
References 39 publications
0
111
0
Order By: Relevance
“…Partially because of its evolutionary implications, much of the interest in unobserved heterogeneity in fitness components focuses on accounting for variance (e.g., Caswell 2011Caswell , 2014Steiner and Tuljapurkar 2012;Vindenes and Langangen 2015;Cam et al 2016;Hartemink et al 2017;van Daalen and Caswell 2017;Jenouvrier et al 2018). In this case, we found that heterogeneity could typically account for less than half of the variance in longevity (35%, with interquartile range 23-44%).…”
Section: Discussionmentioning
confidence: 63%
“…Partially because of its evolutionary implications, much of the interest in unobserved heterogeneity in fitness components focuses on accounting for variance (e.g., Caswell 2011Caswell , 2014Steiner and Tuljapurkar 2012;Vindenes and Langangen 2015;Cam et al 2016;Hartemink et al 2017;van Daalen and Caswell 2017;Jenouvrier et al 2018). In this case, we found that heterogeneity could typically account for less than half of the variance in longevity (35%, with interquartile range 23-44%).…”
Section: Discussionmentioning
confidence: 63%
“…But in general, lifetime offspring production in age‐stage models is a more diverse and nuanced concept than R 0 . Note that much more information about lifetime reproductive output, including variances, higher moments, and sensitivity analysis can be obtained using Markov chains with rewards (Caswell , van Daalen and Caswell , ). The application of these methods to age × stage‐classified models will be explored elsewhere.…”
Section: Population Dynamics: Growth and Structurementioning
confidence: 99%
“…Nonetheless, recent developments in stochastic models (so-called Markov chains with rewards) provide a powerful and general approach to analyzing lifetime reproductive success for age-classified, stage-classified, and multistate models, for any kind of reproductive output distributions, and including a general sensitivity analysis (van Daalen and Caswell 2017). These analyses have shown that the stochasticity within the individual life cycle produces much more variation in lifetime reproductive output than might be expected (Caswell 2011, van Daalen andCaswell 2017), with consequences to be explored at the population level (Caswell and Vindenes 2018).…”
Section: Origin and Maintenance Of Heterogeneity And Its Impacts On Lmentioning
confidence: 99%
“…These analyses have shown that the stochasticity within the individual life cycle produces much more variation in lifetime reproductive output than might be expected (Caswell 2011, van Daalen andCaswell 2017), with consequences to be explored at the population level (Caswell and Vindenes 2018).…”
Section: Origin and Maintenance Of Heterogeneity And Its Impacts On Lmentioning
confidence: 99%